EXAMINING THE CORRELATION BETWEEN ISLAMIC BANKS PROFITABILITY AND THE BUSINESS CYCLE IN INDONESIA - Sholikhin, Mohammad Yusron; Supriani, Indri; Amijaya, Rachmania Nurul Fitri (IJIBE (International Journal of Islamic Business Ethics), 2021)
This study aims to examine the correlation between Islamic banks' profitability in Indonesia and the business cycle, which measured by composite leading Indicator (CLI).Â This study used several annual data covering the period from 2004-2018. This study utilizes Islamic banks profitability represent by Return on Asset (ROA) data as the dependent variable, CLI data as the dependent variable, and six control variables including Gross Domestic Product, Inflation, Financial to Deposit Ratio, Capital Adequacy Ratio, Non-Performing Finance, and Operating Costs Operating Income. This study adopted multiple regression analysis by using EViews 9.0 software. This study reveals that CLI has a positive and significant impact on ROA, which indicated that the expansion of business cycle activities would increase Islamic banks' profitability. Thus, this study suggests that Islamic bank should engage with the companies that relied on their business activities in the rill sector to boost their profitability. The limitation of this study is this study adopted Indonesian Islamic banks in general. Therefore, this study does not capture the correlation amongst the variables in the specific Islamic banks and region, which might be different from this result due to the differences in banks' internal conditions, culture, and the business cycle in the various region.